The coloniality of power and its problematic effects in education - Bautista Velásquez, Aaron Noé (2019)
In this paper we will describe the relationship between the “coloniality of power” and education. Aníbal Quijano developed the concept “coloniality of power” to critically express Latin American thought characterized by its Eurocentric and traditional view. For this we have developed two parts. In the first, we will highlight the importance of the aforementioned concept, in the sense that it is key to explaining the colonized and oppressed reality without implying recourse to the global hegemonic system or its power patterns such as the rationality and modernity of these industrialized societies. In the second we will try to relate this concept with education in our country. In the sense of analyzing the way education deals with certain issues of the colonial heritage, which are currently structural problems, such as discrimination and the inferiority complex, patriarchy and the gender problem. It is concluded that the coloniality of power is a great contribution of Aníbal Quijano that focuses on the hegemonic control that the West has over the rest of the world, which is very current and that generates problematic effects that education reproduces.